An investigation into Communicative English Language Needs and Perceptions of English for Specific Purposes Course: The Case of Holy Trinity Theological College - Birhan, Amare Tesfie (UPI Press, 2019)
This research aimed to investigate the communicative English language needs of Holy Trinity Theological College students. To this end, mixed methods approach was undertaken using questionnaires, interviews and course book (module) analysis. The participants of the study were students, employees, English course instructors, content area instructors. The samples were chosen through availability and purposive sampling. Descriptive statistics and thematic analysis were employed to analyse the data. The findings indicate that students used English language to read and understand professional courses, to communicate freely with English speakers, to prepare religious journals, to present papers in seminaries, to translate books, and to preach the Bible abroad. The respondents preferred courses that contain both professional and academic linguistic items and discourses to use the language in their professional and academic contexts. Furthermore, the text evaluation indicated that the materials were designed without considering theology students’ professional language needs and expectations. Finally, it is recommended that syllabus designers and material writers should consider the communicative English language needs of theology students identified in the study.